Compensating beneficiaries - Eggert, L (Springer Nature, 2024)
This paper illuminates a typically obscured ground for rectificatory obligations: harms justified as ‘lesser evils.’ Lesser-evil harms are not the result of overall morally prohibited acts but of acts permissibly carried out to prevent significantly greater harm. The paper argues that harms caused as unintended side effects of acting on lesser-evil justifications, notably in military rescue operations, may give rise to claims to compensation, even if (1) the military acts that caused the harms in question were justified on lesser-evil grounds and (2) the victims in question are no worse off as a result; they may even owe their survival to the act of rescue. The paper defends three claims. First, being better off as a result of a harmful rescue than one would otherwise have been does not preclude claims to be compensated for harms suffered as a side effect. Second, identifying the relevant counterfactual for purposes of compensatory justice is sometimes a prescriptive, rather than a descriptive, matter. Rather than relying on empirical speculations about what would have happened had a harm not occurred, we must, in certain cases, consider what agents ought to have done. Finally, duties of compensation need not fall on those who caused the to-be-compensated harms. That infringing rights is permissible in certain cases does not imply that no compensation is owed, but merely that it is not necessarily rights-infringers on whom duties of compensation fall.